QUALITY ASSESSMENT OF FOCUSED ANTENATAL CARE SERVICE DELIVERY IN TERTIARY CARE HEALTH FACILITY - Ashraf, Farah; Thaver, Inayat Hussain; Imtiaz, Faisal; Ayub, Adil (Journal of Ayub Medical College Abbottabad, 2017)
Background: Regardless of high maternal deaths in Pakistan, only 37% of pregnant women make four or more antenatal care visits during pregnancy. This proportion has further been diverged between urban and rural. About 62% of women visit clinics for WHO recommended sets of antenatal care (ANC) check-ups in urban as compared to 26% women in rural areas. This study was conducted with the aim to assess quality of Focused ANC service delivery in terms of examination, screening, treatment, counselling and to determine variation in service delivery with provider’s clinical qualification and expertise. Methods: Cross sectional study design was used. Data was collected from pregnant women when they were visiting hospital for their antenatal visits. Direct observation was also made regarding provision of services. Results: Out of 278, 55% of study women were in 28-33 years age group and 21.2% made at least one visit. While 42.8% reported more than one visit, 98.9% received tetanus toxoid, 82% received proper screening. Counselling was done mostly regarding nutrition and self-care (42.8%), and significant association (p-value <0.05) was observed between provider’s clinical qualification and provision of services such as for screening and counselling. Conclusion: The delivery of antenatal care services to pregnant women varied to some extent. Most of the routine investigation services were in accordance with recommended standards of optimal quality with little divergence from guidelines such as screening for HIV and syphilis. Better quality services were being provided to private participants in terms of counselling and danger sign screening. Keywords: Antenatal care; FANC service delivery; Maternal mortality; Optimal Quality